Induction therapy in lung transplantation. (23rd May 2013) - Sweet, Stuart C.
Abstract Strategies for induction in lung transplant recipients typically mirror those used in other solid organ transplant recipients. Polyclonal (Atgam, RATG) and monoclonal (OKT3) T‐cell depleting agents, IL‐2 Receptor antagonists (basiliximab and daclizumab) have been used most commonly. In spite of evidence from ISHLT registry reports that induction reduces acute rejection and has a small benefit in freedom from bronchiolitis obliterans and long‐term survival, other studies have been less convincing in terms of long‐term benefit. Future iterations of induction strategy for lung transplant recipients will hopefully utilize tolerogenic approaches currently being tested in renal transplantation.